How Does Robotic-Arm Assisted Technology Influence Total Knee Arthroplasty Implant Placement for Surgeons in Fellowship Training? - Scholl, Laura Y.; Hampp, Emily L.; de Souza, Kevin M.; Chang, Ta-Cheng; Deren, Matthew; Yenna, Zachary C.; Sodhi, Nipun; Mont, Michael A; Westrich, Geoffrey H. (The Journal of Knee Surgery, 2020)
Implant malalignment during total knee arthroplasty (TKA) may lead to suboptimal postoperative outcomes. Accuracy studies are typically performed with experienced surgeons; however, it is important to study less experienced surgeons when considering teaching hospitals where younger surgeons operate. Therefore, this study assessed whether robotic-arm assisted TKA (RATKA) allowed for more accurate and precise implant position to plan when compared with manual techniques when the surgery is performed by in-training orthopaedic surgical fellows. Two surgeons, currently in their fellowship training and having minimal RATKA experience, performed a total of six manual TKA (MTKA) and six RATKAs on paired cadaver knees. Computed tomography scans were obtained for each knee pre- and postoperatively. These scans were analyzed using a custom autosegmentation and autoregistration process to compare postoperative implant position with the preoperative planned position. Mean system errors and standard deviations were compared between RATKA and MTKA for the femoral component for sagittal, coronal, and axial planes and for the tibial component in the sagittal and coronal planes. A 2-Variance testing was performed using an α = 0.05. Although not statistically significant, RATKA was found to have greater accuracy and precision to plan than MTKA for: femoral axial plane (1.1° ± 1.1° vs. 1.6° ± 1.3°), coronal plane (0.9° ± 0.7° vs. 2.2° ± 1.0°), femoral sagittal plane (1.5° ± 1.3° vs. 3.1° ± 2.1°), tibial coronal plane (0.9° ± 0.5° vs. 1.9° ± 1.3°), and tibial sagittal plane (1.7° ± 2.6° vs. 4.7° ± 4.1°). There were no statistical differences between surgical groups or between the two surgeons performing the cases. With limited RATKA experience, fellows showed increased accuracy and precision to plan for femoral and tibial implant positions. Furthermore, these results were comparable to what has been reported for an experienced surgeon performing RATKA.
Keywords: total knee arthroplasty; training; accuracy; placement